CARDIAC FUNCTION AND IRON CHELATION IN THALASSEMIA MAJOR AND INTERMEDIA: A REVIEW OF THE UNDERLYING PATHOPHYSIOLOGY AND APPROACH TO CHELATION MANAGEMENT - Athanasios Aessopos; Vasilios Berdoukas (Mediterranean Journal of Hematology and Infectious Diseases)
Heart disease is the leading cause of mortality and one of the main causes of morbidity in beta-thalassemia. Patients with homozygous thalassemia may have either a severe phenotype which is usually transfusion dependent or a milder form that is thalassemia intermedia.  The two main factors that determine cardiac disease in homozygous β thalassemia are the high output state that results from chronic tissue hypoxia, hypoxia-induced compensatory reactions and iron overload.  The high output state playing a major role in thalassaemia intermedia and the iron load being more significant in the major form. Arrhythmias, vascular involvement that leads to an increased pulmonary vascular resistance and an increased systemic vascular stiffness and valvular abnormalities also contribute to the cardiac dysfunction in varying degrees according to the severity of the phenotype.  Endocrine abnormalities, infections, renal function and medications can also play a role in the overall cardiac function.  For thalassaemia major, regular and adequate blood transfusions and iron chelation therapy are the mainstays of management. The approach to thalassaemia intermedia, today, is aimed at monitoring for complications and initiating, timely, regular transfusions and/or iron chelation therapy.  Once the patients are on transfusions, then they should be managed in the same way as the thalassaemia major patients.  If cardiac manifestations of dysfunction are present in either form of thalassaemia, high pre transfusion Hb levels need to be maintained in order to reduce cardiac output and appropriate intensive chelation therapy needs to be instituted.  In general recommendations on chelation, today, are usually made according to the Cardiac Magnetic Resonance findings, if available.  With the advances in the latter technology and the ability to tailor chelation therapy according to the MRI findings as well as the availability of three iron chelators, together with increasing the transfusions as need, it is hoped that the incidence of cardiac dysfunction in these syndromes will be markedly reduced.  This of course depends very much on the attention to detail with the monitoring and the cooperation of the patient with both the recommended investigations and the prescribed chelation.